2000
DOI: 10.1006/cbir.2000.0628
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Sendai Virus With Vesicles of Oligomerizable Lipids: A Microcalorimetric Analysis of Membrane Fusion

Abstract: Sendai virus fuses efficiently with small and large unilamellar vesicles of the lipid 1,2-di-nhexadecyloxypropyl-4-(beta-nitrostyryl) phosphate (DHPBNS) at pH 7.4 and 37°C, as shown by lipid mixing assays and electron microscopy. However, fusion is strongly inhibited by oligomerization of the head groups of DHPBNS in the bilayer vesicles. The enthalpy associated with fusion of Sendai virus with DHPBNS vesicles was measured by isothermal titration microcalorimetry, comparing titrations of Sendai virus into (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The amphiphilic compounds DDPBNS and DHPBNS are members of a family of synthetic lipids that provides a useful membrane mimetic system (Ravoo et al, 1996(Ravoo et al, , 1998(Ravoo et al, , 1999(Ravoo et al, , 2000. The molecular structures of DDPBNS and DHPBNS are presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amphiphilic compounds DDPBNS and DHPBNS are members of a family of synthetic lipids that provides a useful membrane mimetic system (Ravoo et al, 1996(Ravoo et al, , 1998(Ravoo et al, , 1999(Ravoo et al, , 2000. The molecular structures of DDPBNS and DHPBNS are presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that fusion of small vesicles is associated with a small positive enthalpy and requires an entropic driving force. Furthermore, the fusion of vesicles of DHPBNS with Sendai virus was investigated (Ravoo et al, 2000). It was observed that vesicle-virus fusion is strongly inhibited by lipid head group oligomerisation.…”
Section: Introductionmentioning
confidence: 99%
“…[162234] As the integral heats of titration do not provide any information on transient states, the heat of fusion of the bilayers per se is small, and the heat effects observed should be mainly attributed to interactions of viral proteins with the target membrane. For example, a partial deprotonation of a viral protein on membrane fusion was detected by ITC using the buffer variation method (see section Isothermal titration calorimetry ).…”
Section: The Effects Of Additives On Membrane Propertiesmentioning
confidence: 99%
“…For example, a partial deprotonation of a viral protein on membrane fusion was detected by ITC using the buffer variation method (see section Isothermal titration calorimetry ). [162] Also the enthalpy of proton-induced vesicle fusion was measured by ITC. [228] DSC studies of viral proteins have yielded important information on fusogenic protein states in viruses (see the next section).…”
Section: The Effects Of Additives On Membrane Propertiesmentioning
confidence: 99%
“…Because of these advantages, the microcalorimetric method may reveal more and newer details about the metabolism than the existing methods do. Therefore, the microcalorimetric method has been used in many fields of biological science [8][9][10]. It can be foreseen that the microcalorimetric technique will be used more and more wildly to understand the biological processes through this technique and other methods.…”
Section: Electron Microscopic Observationmentioning
confidence: 99%